Forward Genetics in Apicomplexa Biology: The Host Side of the Story - Sánchez-Arcila, Juan C.; Jensen, Kirk D. C. (Frontiers in Cellular and Infection Microbiology, 2022)
Forward genetic approaches have been widely used in parasitology and have proven their power to reveal the complexities of parasite-host interactions in an unbiased fashion. Many aspects of the parasite's biology, including the identification of virulence factors, replication determinants, antibiotic resistance genes, and other factors required for parasitic life, have been discovered using such strategies. Forward genetic approaches have also been employed to understand host resistance mechanisms to parasitic infection. Here, we will introduce and review all forward genetic approaches that have been used to identify host factors involved with Apicomplexa infections, which include classical genetic screens and QTL mapping, GWAS, ENU mutagenesis, overexpression, RNAi and CRISPR-Cas9 library screens. Collectively, these screens have improved our understanding of host resistance mechanisms, immune regulation, vaccine and drug designs for Apicomplexa parasites. We also will discuss how recent advances in molecular genetics give present opportunities to further explore host-parasite relationships.